Design method of porous scaffold based on TPMS and KM growth function - Yi Zhang; Jiong Liu; Quan Qi (Graphical Models)
Additive manufacturing technology, as a cutting-edge manufacturing process, has shown great potential in the preparation of 3D tissue engineering scaffolds with complex pore structures. The multi-functional scaffolds produced by this technology can provide a combination of excellent mechanical and biological properties, such as high stiffness, strength, toughness and good fluid permeability. Among many stent design methods, pore shape design based on triply periodic minimal surface is favored because of its advantages in controlling design parameters such as aperture, pore shape and internal channel connectivity. In this paper, a new design method for multi-shape scaffolds is proposed, which combines KM growth function and shape conformal mixing technique to construct a complex pore structure consisting of multiple triply periodic minimal surfaces and arbitrary transition boundaries in a scaffold. The advantage of this method is that it can flexibly control the mixed form of the resulting scaffold, and then explore and optimize a variety of transition pore forms to achieve a combination of multi-functiona characteristics such as high strength and excellent fluid permeability.